Surviving Pandemics: The Role of Spillovers - Meghana Ayyagari; Yuxi Cheng; Ariel Weinberger (Center for Economic Studies and ifo Institute (CESifo), 2022)
What role do spillover effects play in firm resilience during crises? Using high-frequency data on over 7 million import transactions, we ask this question in the context of the large trade disruption faced by US importers in the months immediately following the initial COVID-19 shock. While US firms saw a reduction in imports due to Covid-related trade disruptions to their suppliers, these effects were lower for importers in counties that received greater loans under the Paycheck Protection Program (PPP), a government stimulus program aimed at small businesses. A one standard deviation increase in exposure to PPP reduces the effect of the supply shock faced by the firm by approximately one-fifth. These effects exist even when the importer is not a direct recipient of PPP loans. The effects are largest in counties with larger number of small suppliers and higher input-output industry linkages, and those with greater share of small and medium enterprises (SMEs). We also see similar effects of PPP preserving job growth at the county level even as the trade shock takes a negative toll on local employment. Our results point to local spillovers between SMEs that were PPP recipients and large importers as being an important determinant of firm resiliency during the pandemic.
Keywords: G30; H81; R10; R12; 330; agglomeration spillovers; Paycheck Protection Program; supply chains; Covid-19